Penggunaan Antibodi Anti-idiotipe sebagai Vaksin terhadap Streptokokosis (THE USING OF ANTI-IDIOTYPE ANTIBODY AS VACCINE AGAINST STREPTOCOCCOSIS) - I Nyoman Suartha; Iwan Harjono Utama; Bambang Pontjo Priyosoeryanto; I Wayan Teguh Wibawan (Faculty of Veterinary Medicine, Udayana University and Published in collaboration with the Indonesia Veterinarian Association, 2001)
Abstak dapat dibaca pada Full Text Abstract can be read at Full Text